ANALISIS HUBUNGAN TINDAK AGRONOMI DAN SIFAT KIMIA TANAH TERHADAP PRODUKTIVITAS DAN MINYAK ATSIRI BUNGA MELATI DI KABUPATEN BANJAR - Indriani Indriani; Hilda Susanti; Bambang Fredrickus (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
Banjar Regency in South Kalimantan is the center of jasmine production. The productivity level of the province of South Kalimantan cannot make a large contribution to national jasmine production because the harvested area of South Kalimantan is less competitive than Central Java, this is unforgettable because there are differences in agronomic actions and soil chemical properties. This study analyzed the relationship of agronomic actions and soil chemical properties and the dominant traits affecting the productivity of jasmine in the Banjar Regency. This study adopted survey methods and field observations.The survey method included determining the sampling locations and interviews with jasmine farmers. The selected villages were determined by purposive sampling method by deliberately choosing villages that were dominant in cultivating jasmine plants, namely Labuan Tabu village, Jingah Habang Ilir village, and Pandak Daun village. The results revealed that the agronomy action and soil chemical properties simultaneously had A significant effect on the yield of jasmine. Each of the treatments of nitrogen application, potassium application, and pruning frequency significantly affected the yield of jasmine. The dominant agronomic actions on the yield of jasmine were nitrogen application, pruning frequency, and potassium application, with the contribution of 46.51%, 17.72%, and 17.14%, respectively. The indirect effect of nitrogen fertilizer application channeled through the pruning frequency contributed 18.19% higher than the direct effect of the pruning frequency alone. The indirect effect of potassium fertilizer application through the pruning frequency contributed 16.33% to the jasmine productivity. The application of N fertilizer and the pruning frequency showed a very significant and positive linear relationship to productivity with regression equations of 5.173+0.01526 N and –0.194+3.587 Fpks, respectively.